462. "All Eyes on You": A Covert Observational Study on Contact Precaution Compliance in Six Hospitals at the Detroit Medical Center. (26th November 2018) - Chandramohan, Suganya; Krishna, Amar; Navalkele, Bhagyashri; Virdi, Parminder; Gill, Angad; Javed, Ibtehaj; Mehar, Anupamdeep; Thammineni, Nikhila; Muma, Takwi; Saleem, Aleena; Kazmi, Syed Ali Mehdi; Salma, Ummah; et al.
Abstract: Background: The Center for Disease Control and Prevention recommends strict contact isolation precautions (CP) that include hand hygiene (HH) and barrier (gloves and gown) precautions upon entering and leaving the rooms of patients diagnosed with multidrug-resistant organism or Clostridium difficile infections. Although this policy has been in place for several years, compliance rate among HCW is rarely studied. The aim of our study was to covertly monitor, analyze, and compare the overall bundle compliance (OBC) and individual (HH, glove and gown) component compliance (ICC) among HCWs during routine patient care. Methods: A prospective observational study was done in six Detroit Medical Centers (July 2017 to February 2018). Trained observers audited both inpatient and intensive care units on random days and time. Components audited (1) HH before donning and after doffing (2) gowning and gloving techniques before entering and after existing the patient room. A mobile application (speedy audit) was used to record all data. A pilot targeted education program (TEP) was also conducted in one of the hospitals where education was focused only on strict HH practice before donning. Results: A total of 6, 274 observations were collected. The OBC was 38%. Common HCWs observed included nurses (registered nurse and nursing student) 47%; physicians (attending's, residents, fellows) 28%; service workers including Environmental Service, Food service, Patient transporter, Social worker, Pastoral care- 14%; Allied Health Professions including Dietician, Blood Collection, Physiotherapist, Radiology Tech, Respiratory Therapist 4%; The OBC among all HCW were below 50%. For the ICC, HH (49%) was way below the gloving (80%, ) and gowning (62%) compliance. HH compliance before donning was strikingly lower (40%) than the compliance after doffing (62%). This trend was similar in all HCW. Within a month of TEP, a drastic increase in both HH [↑ to 75% from 26% ( P < 0.001)] and OBC [↑ to 68% from 16% ( P < 0.001)] was seen. Conclusion: Common misconception that gloves are substitute to HH could explain the low HH rates before donning. Recognition of this gap and focused education on HH before donning has led to improved compliance in all HCW. Disclosures: All authors: No reported disclosures.